PENERAPAN MODEL KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN METEMATIKA DI KELAS IX MTS. SWASTA AL WASHLIYAH MEDAN TAHUN PELAJARAN 2014-2015 - MUHAMMAD SALEH (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
The problem in this research is low creativity of the students of the grade IX MTs. AL-Wasliyah Medan on Academic Year 2014-2015 in learning Math. This research is aimed to improve students’ learning result, and the students’ activeness in learning process in cognitive aspects in “kesebangunan” topic by using cooperative learning type STAD. The method used is CAR with four cycles; includes planning, acting, observing, and reflecting. The instrument used are observation guide list of learning process, field note, and objective test. The subject is the 26 students of grade IX MTs.Al-Wasliyah Medan. After analyzing the data, it is showed that there are the improvement of result from the first cycle to the last cycle. It can be seen from the result of test; pre-test (59.92), test on cycle 1 (79.42). Then, the students’ passing grade on the first cyle is 42.31% and on the cycle two is 80.77%. Then, it can be concluded that the using cooperative learning type STAD can improve students’ learning result on “kesebangunan” topic for the great IX MTs. Al-Wasliyah Medan on Academic Year 2014-2015